Unpacking the Research Trends in Flipped Learning through a Bibliometric Lens - Dilo, Asna Usman; Wasiyati, Kristina (English Education Department, 2024)
This bibliometric analysis examines research trends in flipped learning within English as a Foreign Language (EFL) classrooms from 2020 to 2023. Analyzing 930 publications sourced from Google Scholar, the study highlights the steady growth in scholarly interest, peaking in 2022. The findings emphasize the effectiveness of flipped learning in enhancing language skills, student engagement, and learning outcomes, particularly during the COVID-19 pandemic. Highly cited studies underscore the significant impact of this instructional approach. The analysis also explores diverse strategies, models, and technological integrations that contribute to the adaptability of flipped learning in various educational contexts. Despite a slight decline in publications in 2023, flipped learning remains a promising pedagogical method in EFL/ESL education, warranting further exploration and innovation.